Evaluation of a modified internal circulation (MIC) anaerobic reactor for real antibiotic pharmaceutical wastewater treatment: Process performance, microbial community and antibiotic resistance genes evolutions. (August 2022) - Wang, K.M.; Zhou, L.X.; Ji, K.F.; Xu, S.N.; Wang, J.D.
Abstract: Antibiotic pharmaceutical wastewater is a typical high concentration refractory organic wastewater, which may hinder the biological treatment performance. During the treatment, the reactor has the potential to become the hotspot for the spread of antibiotic resistance genes (ARGs). This study evaluated the viability to apply a modified internal circulation (MIC) anaerobic reactor (with external circulation) to real antibiotic pharmaceutical wastewater treatment and further to decipher the microbial diversity and ARGs evolutions. Results indicated over 82%–92% of COD removal efficiency and 80–84% of demeclocycline removal efficiency at HRT of 4 days and 3 days. Additionally, the antibiotics wastewater substantially modified the structure of microbial community. Firmicutes replaced the Bacteroidetes, becoming the predominant bacteria at the phylum level. Methanosaeta was significantly restrained under antibiotic stress while Methanosphaera dominated, suggesting that the predominant methane-production pathway changed from aceticlastic pathway to hydrogenotroph. ARGs evaluation results indicated that higher HRT may increase the risk of ARGs proliferation. The correlation between ARGs and microbial community implied that Comamonas, Enterococcus, Cloacibacillus and Methanosphaera become the potential ARGs hosts and played an important role in ARGs dissemination. Importantly, MIC anaerobic reactor can be successfully applied to demeclocycline antibiotic pharmaceutical wastewater but the risk of ARGs in the sludge should be not neglected. Graphical abstract: Unlabelled Image Highlights: A MIC anaerobic reactor can be applied to treat antibiotic pharmaceutical wastewater. Satisfied COD and antibiotic removal efficiency can be achieved. The predominant methane-production pathway changed from aceticlastic to hydrogenotroph. A higher HRT of the MIC reactor may increase the risk of ARG proliferation. Comamonas, Enterococcus, Cloacibacillus, and Methanosphaera were identified as ARG hosts.